A case report on development of CNS primitive neuroectodermal tumour from astrocytoma - Gupta, Sunnia; Rathore, Narendra (International Journal of Research in Medical Sciences, 2017)
CNS PNET are infrequent in children and very rare in adults. Even rarer is the development of PNET from low grade astrocytoma. We hereby report a case of PNET arising from astrocytoma. Some similar cases have been reported in the past in which radiation was considered to be the etiological factor in the development of PNET from glial neoplasms but in this case the duration of conversion does not go in favour of radiation as the cause.